2019
DOI: 10.1021/acs.jcim.9b00348
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Biologically Active Anticancer Peptides and Their Interactions with Heterogeneous POPC/POPS Lipid Membranes

Abstract: Over the last few decades, anticancer peptides (ACPs) have turned into potential warheads against cancer. Apart from small molecules and monoclonal antibodies, ACPs have been proven to be effective against cancer cells. ACPs are small cationic peptides that selectively bind to the negatively charged cancer cell membrane and kill them by various mechanisms. In the present study, we prepared a random scrambled library of 1200 peptides from the 100 known ACPs and virtually screened them for their anticancer prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…According to Ref. 50 , these two experimentally verified peptides were the most active peptides, and molecular dynamics simulations suggest that they have different interaction mechanisms with heterogenous POPC/POPS lipid bilayer membranes. Whereas the Peptide1 remains adsorbed to the membrane surface, the Peptide2 has membrane penetration capability 50 .…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…According to Ref. 50 , these two experimentally verified peptides were the most active peptides, and molecular dynamics simulations suggest that they have different interaction mechanisms with heterogenous POPC/POPS lipid bilayer membranes. Whereas the Peptide1 remains adsorbed to the membrane surface, the Peptide2 has membrane penetration capability 50 .…”
Section: Resultsmentioning
confidence: 91%
“…It can be observed that Peptide3, which is an active compound too, is lying on a similarity path between Peptide1 and Peptide2. Indeed, Peptide3 is more similar to Peptide1 by the length of their similarity path, and less similar to Peptide2, which is expected since Peptide3 and Peptide1 are analogs of the same peptide 50 . However, despite Peptide2 and Peptide4 are having a common origin, Peptide4 is inactive 50 , and it is not connected to the previous ones in the K-NNG.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations